BIODIVERSITAS FAUNA SEBAGAI SALAH SATU INDIKATOR KESEHATAN HUTAN MANGROVE FAUNA - Rizky Novia Sari; Rahmat Safe'i; Dian Iswandaru (PERENNIAL, 2019)
Mangrove forests have a special function, namely as a green belt which is certainly very important for human life. Health of forests, especially mangrove forests, is often overlooked regarding their health conditions. The health condition of the mangrove forest is very influential on its sustainability, so to know its health, one of the indicators that can be used is fauna biodiversity. Fauna biodiversity can be known by using the FHM (Forest Health Monitoring) method to determine the diversity and condition of health status. Mangrove forest in Pasir Sakti Sub-District, East Lampung Regency has a diversity of 9 species of birds and 5 types of epifauna diversity. Based on this, the Mangrove Forest of Pasir Sakti District, East Lampung Regency has a good forest health status.